Exopolysaccharide produced by potential probiotic Enterococcus faecium MS79: Characterization, bioactivities and rheological properties influenced by salt and pH. (September 2020) - Ayyash, Mutamed; Stathopoulos, Constantinos; Abu-Jdayil, Basim; Esposito, Gennaro; Baig, Mohammad; Turner, Mark S.; Baba, Ahmad Salihin; Apostolopoulos, Vasso; Al-Nabulsi, Anas; Osaili, Tareq
Abstract: Microbial exopolysaccharide (EPS) is of interest due to their applications in food processing and potential health benefits following consumption. The objectives of this study were to: 1) isolate, purify and characterize EPS produced by Enterococcus faecium MS79 (EPS-MS79); 2) investigate bioactive properties of EPS-MS79; and 3) investigate the rheological properties of the EPS-MS79 as influenced by salt type and pH level. The average molecular weight of the EPS-MS79 was 8.3 × 10 5  Da and it is composed of the three monosaccharides arabinose, mannose, and glucose in a molar ratio of 0.8:1.7:11.3. Scavenging activities of EPS-MS79 were 76% and 85% as measured by DPPH and 26% and 44% as measured by ABTS. The antiproliferative activities against colon (72% and 77%) and breast (43% and 56%) cancer cell lines. EPS-MS79 inhibited the growth of bacterial pathogens by up to 3 logs compared to the control. All EPS-MS79 solutions displayed shear thinning behavior. The storage and loss moduli of all EPS-MS79 solutions increased alongside with the frequency increase. Salt type and pH level impacted on the rheological properties of EPS-MS79. The EPS-MS79 could be a potent prebiotic promoting health and rheological properties of foods. Highlights: EPS-MS79 is hetero-exopolysaccharide with unique backbone structure. EPS-MS79 possessed impressive anticancer and antidiabetic properties. The shear-thinning and viscus behaviors were main characters of EPS-M79. It had a noteworthy thermal stability under high temperature.